THE CONCEPT OF CHILDREN'S EDUCATION IN THE PERSPECTIVE OF THE QURAN - Rusdiati, Leni (Faculty of Tarbiyah nad Teacher Training, 2023)
This study aims to analyze the concept of children's education in the perspective of the Koran. In this context, the essence of the meaning of the term tarbiyah becomes the basic foundation of research. This research uses a qualitative approach with a literature study method. Data collection and analysis was carried out using scientific reference materials, including scientific articles, books, proceedings and final assignments (thesis, theses, dissertations) which were tracked via the internet on the google scholar indexer, DOAJ, science direct, and scimago JR. The results of this study found that the concept of child education in the Qur'an contains an element of